STRATEGI KEMITRAAN UMKM PENGOLAH IKAN DI KABUPATEN REMBANG - Anik Nurhidayati; Rikah Rikah (BBM (Buletin Bisnis & Manajemen), 2017)
Strategic partnerships between SMEs processing of dried fish in Rembang is an effort to improve or develop fish processing enterprises capable of high competitiveness and add value in the national market and are able to enter the international market. The technique used in this research is the SWOT matrix, in terms of internal and external. Implementation of this strategy is to develop its production so customers can increase sales with a strong marketing network and partnership among SMEs that are expected to increase.Keywords: swo analisys, partnership